Pendidikan Keagamaan pada Komunitas Anak Jalanan (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Street children are the unlucky society socially and economically. They are alive to decorate the down town in several of its activity. In clean, orderly and secure city, the appearance of street children who are growing bigger is estimated as the disturber. Of course, they have the same right with other child permanently. They have a right in order to get the feasible right, mainly correctly and feasible religion education. But, the religion education for street children is not ever known yet. This research tries to describe the religion education of the street children.
Keywords: street children; religion education; unlucky society